MORPHOLOGICAL FORMATION OF BONE TISSURE IN HYPOPARATHYROIDISM - Gulnoza Ozodovna Khidirova; Musurmonkulov Jahongir Muhammatjonovich (Scholar Express Journals, 2022)
This study is devoted to studying the effect of changes in the functional activity of the parathyroid glands on the morphological intensity of tubular bone formation. Experimental modeling of hypoparathyroidism in laboratory rats (n = 30) wascarried out and the dynamics of morphological changes in the process of tubular bone ossification was analyzed. Based on the results of morphological research methods, the dynamics of the formation of tubular bones is revealed, and the patternsof ossification of bone tissue against the background of hypoparathyroidism are also established. As a result of the study, a difference was shown from the normal histological picture of hypoparathyroid individuals in the growth zones, namely the basal layer, the chondrocytes are vacuolated. The appearance of young osteoblasts is determined in some places; they are arranged as multidirectional architectonics.
Keywords: Parathyroid Gland; Chondrocyte; architectonics; Hypocalcemia